Розкриття взаємовідносин робітничого класу і селянства УРСР (1946-1965 рр.) в радянській науковій літературі другої половини 1960-х - першої половини 1980-х рр. - Нефьодов, Д. В. (Видавництво НДУ ім.М. В. Гоголя, 2017)
У статті проведено аналіз історіографічної розробки радянськими науковцями другої половини 1960-х - першої половини 1980-х рр. взаємозв'язків робітництва та селянства УРСР в період повоєнно- го двадцятиріччя (1946-1965 рр.). Квінтесенцією їх наукових пошуків стала теза про те, що впровадження у виробництво досягнень науки і передової практики, електрифікація, застосування новітніх машин і механізмів змінило характер праці колгоспного селянства - відбулося його максимальне зближення з працею промислового робітника. Даний факт використовувався радянськими істориками для підтвердження ідеологічної концепції стирання граней класових і соціальних відмінностей. У той же час слід відмітити, що радянські дослідники будували свої дослідження на базі джерел, які багато в чому спотворювали реальний стан справ, за паперовими показниками і звітами. В результаті їх висновки все більше розходилися з дійсністю. Незважаючи на достатню кількість праць, створених лише з наукових позицій, всі без винятку радянські дослідники продовжували залишатися всередині радянської "матриці" і вихід з неї міг здійснитися тільки за наявності кардинальних позанаукових стимулів, поява яких відбулася вже у другій половині 1980-х рр.
The article analyzes the historiographical development of interrelations of the Ukrainian SSR workers and peasants during postwar twenty years (1946-1965) by Soviet scientists of the second half of the 1960s-the first half of the 1980s. The subtopic of assistance and cooperation of the working class with the representatives of the Ukrainian village, whose state throughout the Soviet era had the status of "catching up" in its development in comparison with other spheres of the economy and in particular industry, remained objectively relevant in the Soviet historical science of the stagnant era. The restoration of the agricultural sector became one of the most important tasks in the postwar period and, accordingly, this process was actively covered in Soviet literature. The assistance of the working class to the collective farm peasantry in the recovery of agriculture in Ukraine was studied by Soviet scientists of the second half of the 1960s - the first half of the 1980s in four following directions: a) the participation of workers of the tractor and agricultural machinery industry of Ukraine in the struggle for technical equipment of agriculture; b) the assistance of the working class in upgrading of the material and technical basis of the collective-farm production; c) the participation of the working class in the upgrading of machinery and tractor stations and collective farms by skilled personnel; d) the role of the working class in conducting political and cultural-mass work in the Ukrainian village. The quintessence of their scientific research was presented by the thesis that the introduction of scientific advances and best practices into production, motorization, the use of new machines and mechanisms changed the work pattern of the collective farm peasantry, i.e. it became similar to the work pattern of an industrial worker. This fact was used by Soviet historians to confirm the ideological concept of blurring the boundaries of class and social differences. At the same time it should be noted that the researchers built their investigations on the basis of sources which in many respects distorted the real state of affairs, according to paper rates and reports. As a result, their conclusions increasingly disagreed with reality. Despite a sufficient number of works created exclusively in science terms, all researchers without exception continued to remain within the Soviet "matrix" and could leave it only due to the presence of cardinal unscientific incentives, the emergence of which took place already in the second half of the 1980s.
Keywords: УРСР; робітничий клас; повоєнна відбудова; Ukrainian SSR; working class